AIR LIMBAH INDUSTRI BIOETANOL BERBAHAN BAKU UBI KAYU SEBAGAI BAHAN BAKU PRODUKSI BIOGAS - Mulyanto, Adi (BPPT)
As a tropical country, Indonesia has riches of biomass. Cassava is one of biomass which contains plenty of carbohydrate. Carbohydrate then is utilized as a source for producing bioethanol. In producing of bioethanol, the process also yield side product named vinasse. Vinasse is produced from distillation process of solution containing ethanol which has concentration between 7 and 10%. Vinasse contents very high organic substances with COD and BOD concentration amounting of 30,000 mg/L and 27,000 mg/L respectively. Vinasse was then treated in an anaerobic process by using fixed bed digester. Anaerobic fixed bed digester volume was 225 L. The digester was provided with support materialsmade from cutted PVC pipe. The support materials has void volume of 93%. Therefore, the effective volume of the digester was 209 liters. The digester was operated by upflow mode. Research result from this experiment will be utilized as basic design for producing biogas at a bioethanol plant located in Lampung Tengah. Capacity of the plant is 8,000 litres of bioethanol per day. Whereas the vinasse produced is 100,000 litres per day.Keywords: bioethanol, vinasse,fixed bed digester, biogas, casava waste water